However In Social Science Research Articles Written By Indonesian Writers - Fitriyatuz Zakiyah (Experimental Student Experiences, 2023)
This article analyzes the distribution of however in research articles written by Indonesian writers. The source of the data was 50 research articles from International journals of social sciences indexed by Scopus written by Indonesian writers from 2020-2022. This study used qualitative method since this study classified and described the place of however in sentences in the data. The result showed that however was commonly applied in initial sentences. It was never applied at the end of sentences. This implies that Indonesian researchers do not apply sentence connectors at the end of sentences as in Indonesian language, no conjunctions are placed at the end of the sentence. Thus, this study gives evidence that there is L1 transfer in L2 writing.